PENERAPAN SANKSI PIDANA TERHADAP PELAKU KEKERASAN YANG DILAKUKAN OLEH PELAJAR (Studi Putusan Nomor 38/Pid.B/2020/PN Skl) - sukran sukran; Joelman Subaidi; Muhibuddin Muhibuddin (Fakultas Hukum Universitas Malikussaleh, 2022)
Violence is basically an aggressive action that can be done by anyone. Violence is a form of crime that is against the law. Violence committed by students or students with a background of persuasion and because of the development of an unstable mental attitude, must be treated the same as adults. Humanely, treatment must be distinguished, because physically and mentally, they are different from adults. Based on the background of the problem, it is formulated that the problem is how to apply criminal sanctions against perpetrators of violence and how are victims and perpetrators responding to the judge's decision number 38/Pid.B/2020/PN Skl.The law is a norm and rule, a crime is a form of deviant behavior that is always attached and will continue to develop in people's lives, the victim is a person who has suffered physical or mental suffering, while the perpetrator is a person who intentionally commits an intentional act.The research method used in this thesis is using sociological juridical research. Empirical juridical method is a type of research in research which in other words is a type of sociological legal research and can also be called field research, namely a case approach. The nature of descriptive research, data analysis. The research location is in the Singkil District Court, the sample consists of informants and respondents. Sources of data in this study are primary data and secondary data.Based on the results of the research that the author did, it is known that: 1) The application of sanctions for criminal acts of violence committed by students is not in accordance with the decision letter because where students are categorized as children, especially cases of violence that occur within the school environment, the school should solve the problem. 2) The response of the victim and the perpetrator to the judge's decision where the victim agreed and of the three perpetrators all disagreed because they thought they should not be imprisoned because their status was still in school and still attending lessons.Suggestions from researchers are: 1) The government in charge should conduct socialization to schools, especially high schools where in order to reduce the occurrence of violent crimes committed by students and other criminal acts. 2) Parents should pay more attention and provide guidance to their children to be careful in doing something that can violate the law as well as by providing sufficient understanding of the dangers of violent criminal acts which are detrimental to themselves. 3) Teachers should pay more attention to the activities of students in the school environment or around the school.